2005
DOI: 10.1105/tpc.105.034645
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the Vernalization-Responsive, Winter-Annual Habit inArabidopsisRequires a Putative Histone H3 Methyl Transferase[W]

Abstract: Winter-annual accessions of Arabidopsis thaliana are often characterized by a requirement for exposure to the cold of winter to initiate flowering in the spring. The block to flowering prior to cold exposure is due to high levels of the flowering repressor FLOWERING LOCUS C (FLC). Exposure to cold promotes flowering through a process known as vernalization that epigenetically represses FLC expression. Rapid-cycling accessions typically have low levels of FLC expression and therefore do not require vernalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
220
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(238 citation statements)
references
References 54 publications
14
220
2
2
Order By: Relevance
“…These regions are essential for FLC transcription and function (Bastow et al, 2004;Kim et al, 2005), and H3K4me3 marks in these regions correlate with FLC transcription (He et al, 2004). We found that H3K4me3 levels were reduced in region B and undetectable in region A in atx1-1 mutants ( Figure 4B) compared with wild-type plants at the same developmental stage.…”
Section: Atx1 Is Required For the Deposition Of H3k4me3 Marks At Thementioning
confidence: 57%
See 1 more Smart Citation
“…These regions are essential for FLC transcription and function (Bastow et al, 2004;Kim et al, 2005), and H3K4me3 marks in these regions correlate with FLC transcription (He et al, 2004). We found that H3K4me3 levels were reduced in region B and undetectable in region A in atx1-1 mutants ( Figure 4B) compared with wild-type plants at the same developmental stage.…”
Section: Atx1 Is Required For the Deposition Of H3k4me3 Marks At Thementioning
confidence: 57%
“…The putative HMT EARLY FLOWERING IN SHORT DAYS (EFS), a homolog of the trxG Drosophila protein Absent small homeotic disks1 (ASH1) (Tripoulas et al, 1994), was shown to be necessary for the deposition of H3K4me3 marks at FLC chromatin of winter annual accessions (He et al, 2004). In such accessions, vernalization (extended exposure to cold) is required to activate the VRN Polycomb Repressive Complex 2 (VRN-PRC2) (Levy et al, 2002;Kim et al, 2005), which represses FLC, leading to flowering. However, in the commonly studied rapid-flowering accession Col, vernalization is not required for flowering, and mutations in EFS do not affect the level of H3K4me3 at the FLC locus (He et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A few putative target genes responsible for these phenotypes have been described and target gene loci show a lower abundance of H3K4 or H3K36 methylation marks, as well as reduced mRNA levels in the sdg8 mutant. However, only the early flowering and lutein deficient phenotypes have been sufficiently complemented by overexpression of the corresponding target genes, FLOWERING LOCUS C (FLC) and CRTISO, respectively (Kim et al 2005;Cazzonelli et al 2009a). The affect of the chromatin marks can spread and appear to only have a slight affect on the relative transcript abundance of genes neighbouring CRTISO and FLC, suggesting that indeed both CRTISO and FLC are likely to be direct targets of SDG8 activity (Kim et al 2005;Cazzonelli et al 2009a).…”
Section: Epigenetic Maintenance Of Carotenoid Compositionmentioning
confidence: 99%
“…The sdg8 mutant shows several pleiotropic phenotypes, such as early flowering, altered shoot and root architecture, altered pathogen resistance, male sterility, abnormal sporophyte and gametophyte development (Kim et al 2005;Cazzonelli et al 2009a;Grini et al 2009;Berr et al 2010). A few putative target genes responsible for these phenotypes have been described and target gene loci show a lower abundance of H3K4 or H3K36 methylation marks, as well as reduced mRNA levels in the sdg8 mutant.…”
Section: Epigenetic Maintenance Of Carotenoid Compositionmentioning
confidence: 99%
“…EARLY FLOWERING IN SHORT DAYS (EFS, also known as SDG8) is the major contributor for H3K36 methylation in Arabidopsis (Kim et al, 2005;Zhao et al, 2005). Cheng et al uncover a novel function of EFS/SDG8 in embryogenesis (Cheng L. et al, 2018).…”
Section: Histone and Dna Modifications: An Ever-growing Puzzlementioning
confidence: 99%